Parenting Paradigms in Islamic Educational Philosophy: Reconstructing The Concept of Parenting Amidst The Challenges of Modernity - Rahayu, Evi (Cyber Media Indonesia, 2026)
This study examines parenting paradigms in Islamic educational philosophy and reconstructs the concept of parenting amidst the challenges of modernity, particularly in the digital era. The research adopted a qualitative approach with a multi-family case study design involving Muslim families in two major cities in Indonesia who actively use digital technology and have pre-teen children. Data collection was conducted through in-depth interviews, participant observation, and document analysis, while thematic analysis was employed to identify recurring patterns and themes. The findings reveal that Muslim families employ various adaptive strategies in child-rearing within the digital age. First, 85% of families maintain regular congregational prayers, and 70% allocate specific time for Quran study, positioning the home as the